Using a Multimedia Tool for Informed Consent in Mohs Surgery: A Randomized Trial Measuring Effects on Patient Anxiety, Knowledge, and Satisfaction. Issue 5 (May 2020) - Delcambre, Macey; Haynes, Dylan; Hajar, Tamar; Golden, Spring; Bar, Anna; Latour, Emile; Leitenberger, Justin J.
Abstract : BACKGROUND: Multimedia educational materials have been found to improve aspects of informed consent, although data in the context of Mohs micrographic surgery (MMS) is limited. OBJECTIVE: To assess whether a preoperative educational video decreases anxiety, increases comprehension, and improves overall satisfaction for patients undergoing same-day office consultation and MMS. MATERIALS AND METHODS: This single-center randomized controlled trial included patients above the age of 18 years undergoing MMS for skin cancer between October 2015 and December 2015. Patients were randomized to view a short preoperative video on MMS in addition to traditional informed consent versus informed consent without video viewing. Questionnaires were used to assess preoperative anxiety, knowledge, and satisfaction. RESULTS: From 231 consecutively enrolled subjects, there were no significant differences in anxiety ( p = .626) or satisfaction ( p = .065) between groups. Subjects receiving the intervention were able to more accurately recognize risks of MMS (88% vs 69% of controls, p < .001) and had improved subject-reported confidence in understanding procedural risks and benefits (89% vs 71% of controls, p = .049). Composite comprehension scores were similar between groups ( p = .131). CONCLUSION: A preoperative MMS educational video increased recognition of procedural risks, but did not improve patient anxiety or satisfaction. Abstract : Supplemental Digital Content is Available in the Text.